EFFECT OF GRAPE SEED EXTRACT SOLUTION ON THE MICROHARDNESS OF THE ROOT CANAL DENTIN: AN IN VITRO STUDY - ALINDA, SYLVA; MARGONO, ANGGRAINI; ASRIANTI, DINI (International Journal of Applied Pharmaceutics, 2020)
Objective: Grape seed extract (GSE) containing proanthocyanidin as a root canal irrigation solution has its antibacterial effects and ability to eliminate the smear layer. In addition, proanthocyanidin acts as a cross-linking agent of collagen, which adds to dentin’s mechanical properties. This study analyzed the effect of GSE containing 2.9% proanthocyanidin on the microhardness of the dentin in the root canal. Methods: Fifty teeth were divided into three groups and immersed in GSE solution, 3% NaOCl solution, or distilled water (controls) for 30 min for 3 consecutive days. The microhardness was measured using the Vickers method. Data were analyzed using the Kruskal–Wallis test. Results: The GSE group presented the highest microhardness values, whereas the lowest values in the NaOCl group. No significant difference in microhardness observed between the GSE and distilled water groups. Conclusion: The GSE solution maintains the microhardness of the root canal dentin.